The second All-Union summer school of homotetical topology - Journal, Lithuanian Mathematical (Lithuanian Mathematical Journal, 1966)
Original title in Russian and Lithuanian:Вторая Всесоюзная летняя школа по гомотопической топологииAntroji Visasąjunginė homotetinės topologijos vasaros mokykla